Discovering water relations using hydrochemistry, isotopic data, and mass-balance calculation approaches to reduce the risk of impacts from limestone mining - Poetra, Reinaldy Pratama (Elsevier B.V., 2023)
This study aims to determine whether limestone mining does not affect the sustainability of the springs in the vicinity. We simulated the linkages between several water sources in the prospective limestone mining area and its surroundings with various geological formations. The approach in this study is by integrating hydrochemical analysis, isotope data, and mass-balance calculations to understand the hydrological system's linkages in a geologically complex area, particularly in the proposed limestone mining site. Twenty-two samples for hydrochemical and isotopic analysis were taken spatially (in each geological formation) to represent various water sources: springs, caves, shallow groundwater, and deep groundwater. Hydrochemical analysis indicates that both caves and springs have a low degree of mineralization and mostly simple facies (Ca–HCO3). Further, both have lighter isotope values (δ18O and δ2H), meaning they are relatively younger and have not experienced advanced hydrochemical processes. Yet, the most interesting point is that the mass-balance modelling shows the bold information that the southern caves are not related to the springs. It is due to the mismatch between the thermodynamic calculation and the actual condition. The southern caves are primarily supplied by rainwater, where >95 of the ions are evolved due to water-rock interaction, while the springs receive recharge from rainwater (40) and other systems. Synthesizing the information, we hypothesize that mining the limestone in the southern part (consisting of the caves) will not disturb the springs as they are unrelated. © 2023 Elsevier B.V.